10.1146/annurev-nutr-072610-145121 (CrossRef Listing of Deleted DOIs, 2000)
Spatial metabolomics has emerged as a transformative approach for understanding how metabolism is organized within tissues and how nutritional factors influence health and disease. By preserving the spatial context of metabolites within intact tissue architecture, techniques such as MALDI and DESI imaging mass spectrometry reveal metabolic heterogeneity that bulk analyses cannot capture. This review examines how spatial metabolomics advances nutrition research across multiple domains: from mapping nutrient distributions in foods to understanding how diet reshapes tissue metabolism in disease states. We highlight recent innovations, including single-cell-resolution imaging, 3D metabolome reconstruction, stable isotope tracing, and multiomics integration. Key applications demonstrate how dietary patterns drive glycogen accumulation in cancer, alter lipid zonation in fatty liver disease, and modulate brain metabolism through the gut-brain axis. These spatially resolved insights establish direct mechanistic links between nutrition, tissue metabolism, and disease pathogenesis.